Teaching I-O psychology to undergraduate students: Do we practice what we preach?. Issue 4 (December 2020) - Kath, Lisa M.; Salter, Nicholas P.; Bachiochi, Peter; Brown, Kenneth G.; Hebl, Mikki
Abstract: As industrial-organizational (I-O) psychologists, we have expertise in applying psychological and/or organizational science to the workplace. However, many of us haven't taken the time to think about how our I-O psychology knowledge can apply to our teaching practice. We walk through some examples of how I-O psychology research can help us be better teachers, and the goal of our paper is to encourage readers to make evidence-based changes to their teaching based on I-O psychology research. We organize our discussion around four areas: training and development, diversity and inclusion, groups and teams, and leadership. Within each, we offer small, medium, and large changes that could be incorporated into classrooms. We hope that readers will be inspired to build on what they do in their classrooms to help students learn about (and be inspired by) our field.